Media Sosial Sebagai Strategi Pencegahan Tawuran Pelajar - Margaret, Monica; Marifatullah, Awaluddin (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2022)
This study discusses about student brawls which are a bad tradition that has been passed down until now unresolved, the role of alumni is very influential on the new generation in the school. In the era of technological development, technology is developing very rapidly so that it makes it easier for users to express themselves, both expressing in a positive and negative direction. Student brawls that follow technological developments are now widespread in social media circles which cause violent content to emerge. The role of alumni and the community outside the police unit who work together in preventing these brawls by utilizing social media as a forum for preventive action and stop brawl campaigns. This research was conducted with a qualitative approach and descriptive method using primary data obtained from interviews with students about the stop brawl campaign using Social Control Theory (Social Bond Theory) along with Social Crime Prevention Theory so as to suppress the intention for these consumers not to commit crimes, brawl with prevention carried out from the elements of society